2003
DOI: 10.3201/eid0912.020733
|View full text |Cite
|
Sign up to set email alerts
|

Human Monocytotropic Ehrlichiosis, Missouri

Abstract: To determine the incidence, clinical and laboratory characteristics, and utility of molecular diagnosis of human monocytotropic ehrlichiosis (HME) in the primary care setting, we conducted a prospective study in an outpatient primary care clinic in Cape Girardeau, Missouri. One hundred and two patients with a history of fever for 3 days (>37.7°C), tick bite or exposure, and no other infectious disease diagnosis were enrolled between March 1997 and December 1999. HME was diagnosed in 29 patients by indirect imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 25 publications
(19 reference statements)
1
92
0
3
Order By: Relevance
“…11,15,24 However, in another study, a substantial number of confirmed cases of HME had undetectable ehrlichial DNA by PCR. 25 Because of the limited data available and lack of a standard PCR protocol, current recommendations for the diagnosis of HME suggest that PCR is a valuable adjunct to IFA. 26 Nevertheless, more studies are needed to unequivocally determine the clinical sensitivity of PCR during initial presentation in the primary care setting.…”
Section: Discussionmentioning
confidence: 99%
“…11,15,24 However, in another study, a substantial number of confirmed cases of HME had undetectable ehrlichial DNA by PCR. 25 Because of the limited data available and lack of a standard PCR protocol, current recommendations for the diagnosis of HME suggest that PCR is a valuable adjunct to IFA. 26 Nevertheless, more studies are needed to unequivocally determine the clinical sensitivity of PCR during initial presentation in the primary care setting.…”
Section: Discussionmentioning
confidence: 99%
“…Case-fatality rates are highest among children aged <10 years and adults aged ≥70 years, and an increased risk for death has been documented among persons who are immunosuppressed (5,13). In areas where ehrlichiosis is endemic, the actual disease incidence is likely underrepresented in estimates that are based on passive surveillance (51)(52)(53).…”
Section: Ehrlichiaementioning
confidence: 99%
“…Although older age (≥60 years) and immunosuppression are risk factors for severe ehrlichiosis (5,10,13), many cases of severe or fatal ehrlichiosis have been described in previously healthy children and young adults (128). Pediatric patients frequently have an asymptomatic or a mild infection (51,128,132); however, children aged <10 years have the highest case-fatality rate among passively reported cases (5,13). Receiving a sulfonamide antimicrobial agent might also predispose to severe ehrlichial illness (150)(151)(152)(153).…”
Section: Clinical Coursementioning
confidence: 99%
See 2 more Smart Citations